The Role of HNF1B in Tumorigenesis of Solid Tumours: a Review of Current Knowledge - Bártů, M; Dundr, P; Němejcová, K; Tichá, I; Hojný, H; Hájková, N (Folia biologica, 2018)
Hepatocyte nuclear factor 1-β is a transcription factor which plays a crucial role during ontogenesis in the differentiation of visceral endoderm from primitive endoderm, and is especially important for the normal development of the kidney, urogenital tract, gastrointestinal tract, liver, and pancreas. Despite the growing knowledge about the potential involvement of hepatocyte nuclear factor 1-β in the process of carcinogenesis, the exact underlying mechanism that would explain its rather varied effects in different tumours has not been sufficiently investigated. Most of the data regarding the significance of hepatocyte nuclear factor 1-β arise from genome- wide association studies and is concerned with the influence of single-nucleotide polymorphisms of hepatocyte nuclear factor 1-β on either the increased or decreased susceptibility to certain types of cancer. However, the influence of both the germinal and somatic mutations of this gene on the process of carcinogenesis is still poorly understood. According to current data, in some tumours hepatocyte nuclear factor 1-β acts as a protooncogene, while in others as a tumour suppressor gene, although the reasons for this are not clear. The exact incidence of hepatocyte nuclear factor 1-β mutations and the spectrum of tumours in which they may play a role in the process of carcinogenesis remain unknown. From the practical point of view, immunohistochemical expression of hepatocyte nuclear factor 1-β can be used in differential diagnostics of certain tumours, especially clear cell carcinoma. In our article we review the current knowledge regarding the significance of hepatocyte nuclear factor 1-β in carcinogenesis.
Keywords: Hepatocyte Nuclear Factor 1-beta; Protein Isoforms; hepatocytární jaderný faktor 1-beta; nádory; Carcinogenesis; zárodečné buňky; Germ Cells; Animals; lidé; Neoplasms; Biomarkers, Tumor; protein - isoformy; nádorové biomarkery; zvířata; Humans; karcinogeneze